Nursing Education Research Groups in Brazil - Backes, Vânia Marli Schubert; Prado, Marta Lenise do; Lino, Mônica Motta; Ferraz, Fabiane; Reibnitz, Kenya Schmidt; Canever, Bruna Pedroso (Revista da Escola de Enfermagem da USP, 2012)
The aim of this study is to characterize the organization of nursing education research groups in Brazil. This is a quantitative, descriptive and documentary study. Census data for 2006 were collected from the CNPq database website. Brazil has 47 education research groups, comprised of 412 researchers, of whom 91% have masters, doctoral or postdoctoral degrees. There are 307 students, of whom 92% are nursing undergraduates. However, only 9% are recipients of young investigator grants. There are also 112 technicians, of whom 75% are nursing professionals; 46% have a masters or doctoral degree. In Brazil, there are a considerable number of nursing education research groups, which contribute significantly to scientific production of nursing knowledge in Latin America. In this scenario, there are many challenges to be overcome: poor interdisciplinary cooperation; limited integration between education and practice; low number of grants awarded to young investigators and significant inequalities between the country's geographic regions in terms of access to research development.